Simulation tools for FACTS devices optimization problems in electrical power systems - Mansoor Alturki; Ismail Marouani (AIMS Energy)
Technological advancements and ongoing scientific research have significantly contributed to addressing challenges within electrical networks. The emergence of FACTS (Flexible AC Transmission Systems) devices has introduced new opportunities for enhancing the safety and efficiency of these networks. A key focus for researchers in this domain has been optimizing FACTS devices, particularly in terms of identifying the most suitable locations, sizes, and types of controllers within electrical systems. The advent of simulation software has played a crucial role in the evolution of electrical and electronics engineering. Both offline and real-time simulation tools have gained traction in recent years, proving essential for the effective management of power systems and FACTS controllers. In this paper, we present a comprehensive overview of modeling, classification, and simulation-based approaches to various optimization challenges associated with FACTS controllers. We examined a range of simulation platforms, including MATLAB/Simulink, PSAT, EMTDC/PSC etc., assessing their effectiveness in evaluating the performance of optimized FACTS controllers and their dynamic interactions within power networks.